2019
DOI: 10.1016/j.regen.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

An elastin-based vasculogenic scaffold promotes marginal islet mass engraftment and function at an extrahepatic site

Abstract: In islet transplantation, one of the major obstacles to optimal engraftment is the loss of islet natural vascularization and islet-specific extracellular matrix (ECM) during the islet isolation process. Thus, transplanted islets must re-establish nutritional and physical support through formation of new blood vessels and new ECM. To promote this critical process, we developed an elastin-based vasculogenic and ECM-promoting scaffold engineered for extrahepatic islet transplantation. The scaffold by design consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…The transplant efficacy of ITx using white adipose tissue is unclear. However, some groups have successfully achieved normoglycemia using the epididymal fat pad by one donor [49,53,56] and others by more than two donors [42,50,52,55,[62][63][64][65]67]. In our experience, 200 islets can be obtained from a single mouse.…”
Section: Previous Trials Using White Adipose Tissue As a Transplant Site For Islet Transplantationmentioning
confidence: 93%
See 1 more Smart Citation
“…The transplant efficacy of ITx using white adipose tissue is unclear. However, some groups have successfully achieved normoglycemia using the epididymal fat pad by one donor [49,53,56] and others by more than two donors [42,50,52,55,[62][63][64][65]67]. In our experience, 200 islets can be obtained from a single mouse.…”
Section: Previous Trials Using White Adipose Tissue As a Transplant Site For Islet Transplantationmentioning
confidence: 93%
“…Although the epididymal fat pad has the disadvantage of systemic insulin release, it has been used for the experimental ITx studies instead of the omentum because of its ease in operability (Figure 1). Many studies have shown its usefulness in assessing various types of bioscaffold, including elastin [49], fibrin [50], poly(lactide-co-glycolide) [51][52][53][54], polyethylene glycol [13,42,[55][56][57], alginate (ALG) [58,59], and poly-l-lysine [60], much like the omentum (Table 3). Unlike in rodents, dogs, and monkeys, subcutaneous tissue in humans is composed of connective tissue and white adipose tissue.…”
Section: Previous Trials Using White Adipose Tissue As a Transplant Site For Islet Transplantationmentioning
confidence: 99%
“…The importance of extracellular matrix (ECM) components such as collagen, laminin and fibronectin for islet function has been demonstrated, signifying their critical role in organizing networks between endocrine cells, vascular endothelial cells, neural cells and immune cells [ 50 , 51 , 52 , 53 ]. These interactions facilitate the rapid signalling between the islet graft and host tissues, which enables graft survival, viability, restored insulin secretion and tissue remodelling [ 50 , 54 ]. During the enzymatic and mechanical digestion process inherent in islet isolation, the native ECM and the vasculature are disrupted [ 55 ], thus leading to a decrease in cell viability and suboptimal transplant outcomes [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Elastin may produce these effects by altering the differentiation of fibroblasts into contractile myofibroblasts [5][6][7] and promoting new elastin expression in a healing wound [8][9][10]. In addition, elastin has been shown to enhance angiogenesis [11,12]. Even though elastin has demonstrated positive effects on dermal function and regeneration, its insolubility drawbacks in three-dimensional bioscaffold construction remain underexplored.…”
Section: Introductionmentioning
confidence: 99%